Alfateema Business Communication Strategy in Increasing Consumer Loyalty - Renita Kurnia; Bahariandi Aji Prasetyo; Novrizon Marzal (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Online business requires business communication that is useful for persuading potential consumers while making existing consumers loyal. One of the UMKM brands that uses business communication is Alfateema. The purpose of this research is to determine Alfateema's business communication strategy for increasing consumer loyalty. This research uses a qualitative descriptive method by collecting data through observation, interviews, and literature studies. The data analysis technique uses source triangulation. This research uses elements of communication, 7C business communication principles, and consumer loyalty characteristics. Alfateema builds relationships with consumers and increases loyalty through effective communication that the company owns across various platforms. The business employs communication principles such as completeness, conciseness, courtesy, and consideration to achieve this, as revealed by the results of the research. Then the business communication carried out by Alfateema produces a positive reputation so that consumers turn into loyal customers and faithfully use Alfateema products by making repeat buyers, recommending to others, and demonstrating immunity to the full competition.